Sales Strategy Of Wuling Almaz Vehicles To Millennial Generation (Case Study At Wuling Arista Bogor Showroom) - Muhammad Fauzi Hidayat; Sutopo Sutopo (Green Publisher Indonesia, 2024)
This research explores the effective sales strategy of Wuling Almaz vehicles among the Millennial Generation, with a focus on the Wuling Arista Bogor showroom. Through a qualitative approach, this research evaluates the preferences and needs of the Millennial Generation in purchasing vehicles and analyzes the effectiveness of the Wuling Almaz Vehicle sales strategy on the Millennial Generation. The results illustrate that the sales strategy of Wuling Almaz Vehicles is positively successful with the Millennial Generation.